2017
DOI: 10.1002/cbdv.201700095
|View full text |Cite
|
Sign up to set email alerts
|

UHPLC/HRESIMS/MS Profiling of Phenolics from Tunisian Lycium arabicum Boiss. Antioxidant and Anti‐lipase Activities’ Evaluation

Abstract: This study was performed in the aim to evaluate nine different extracts from Tunisian Lycium arabicum for their total phenolic and total flavonoid contents, phytochemical analyses as well as their antioxidant and anti-lipase activities. The in vitro antioxidant property was investigated using three complementary methods (DPPH, ferric reducing antioxidant power (FRAP), and β-carotene-linoleic acid bleaching assays) while anti-lipase activity was evaluated using 4-methylumbelliferyl oleate method. From all of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 62 publications
2
13
0
Order By: Relevance
“…Flavonols were the most abundant phenolic compounds in goji stems, although mostly due to the presence of quercetin-3-O-rutinose (rutin, peak 16), with minor levels of kaempferol-3-O-rutinose (peak 20). The presence of rutin as a major flavonol in different parts of goji plants has been consistently reported by several authors (Affes et al, 2017;Bondia-Pons et al, 2014;Mocan et al, 2017Mocan et al, , 2015aMocan et al, ,b, 2014Protti et al, 2017;Qian et al, 2004;Zhang et al, 2016). Flavonols were less abundant in the fruits, despite they presented greater variety of these compounds.…”
Section: Individual Phenolic Profilesupporting
confidence: 56%
See 1 more Smart Citation
“…Flavonols were the most abundant phenolic compounds in goji stems, although mostly due to the presence of quercetin-3-O-rutinose (rutin, peak 16), with minor levels of kaempferol-3-O-rutinose (peak 20). The presence of rutin as a major flavonol in different parts of goji plants has been consistently reported by several authors (Affes et al, 2017;Bondia-Pons et al, 2014;Mocan et al, 2017Mocan et al, , 2015aMocan et al, ,b, 2014Protti et al, 2017;Qian et al, 2004;Zhang et al, 2016). Flavonols were less abundant in the fruits, despite they presented greater variety of these compounds.…”
Section: Individual Phenolic Profilesupporting
confidence: 56%
“…Three chlorogenic acids, peaks 2, 4 and 7 showing a pseudomolecular ion [M−H] − at m/z 353 yielding a main product ion at m/z 191 (deprotonated quinic acid), were identified as cis and trans 3-O-caffeoylquinic acids and trans 5-O-caffeoylquinic acid, respectively, based on the hierarchical keys previously described by Clifford et al (2003Clifford et al ( , 2005. These type of compounds are among the most common phenolic compounds usually reported in goji samples, although most authors do not indicate the particular derivative, but just refer to them as chlorogenic acid or isomers (Affes et al, 2017;Bondia-Pons et al, 2014;Donno et al, 2015;Mocan et al, 2015aMocan et al, ,b, 2014Qian et al, 2004;Zhang et al, 2016;Zhou et al, 2017). Only Mocan et al 2017 dwdry weight basis; ndnot detected.…”
Section: Individual Phenolic Profilementioning
confidence: 99%
“…Compound 39 , with [M − H] − ion at m / z 312, presented fragment ions at m / z 297, 178, and 135, typical of caffeoyltyramine derivative [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Journal of Analytical Methods in Chemistry fragment ions at m/z 173 (base peak), m/z 155, and m/z 111[19].Compound presented [M − H] − ion at m/z 315 and suffered the neutral loss of a hexoside moiety (162 Da), obtaining the typical fragmentation of hydroxytyrosol (m/z 153, 135, and 123).is compound was named as hydroxytyrosol-O-hexoside[20].Compound 13 was identified as benzyl alcohol hexose pentose (formate adduct) with [M − H] − ion at m/z 447 and fragments at m/z 401 (neutral loss of HCl), m/z 269 (neutral loss of pentoside molecule, 132 Da), and m/z 161 (neutral loss of benzyl alcohol, 108 Da) corresponding with a hexoside[21].Compound 18 (m/z 342) was characterized as magnoflorine using the positive ion mode. is alkaloid presented the base peak at m/z 297, and other fragment ions at m/z 282 and 265[22].Compound 39, with [M − H] − ion at m/z 312, presented fragment ions at m/z 297, 178, and 135, typical of caffeoyltyramine derivative[23].…”
mentioning
confidence: 99%
“…Since a lot of phenolic compounds (phenylpropanoids, dicaffeoylspermidine/dicaffeoyl-spermine derivatives, phenolic amides, flavonoids) were found in the extracts, their antioxidative activities were compared using 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2’-azinobis-(3-ethyl-benzthiazoline-6-sulphonate) (ABTS) and ferric reducing ability of plasma (FRAP) assays [49,50]. The results demonstrated that all the extracts showed antioxidative activities (Table 3).…”
Section: Resultsmentioning
confidence: 99%